Short-Run Equilibrium and Stability in the Two-Sector Growth Model - Chacholiades, Miltiades (Econometrica, 1974)
[This paper demonstrates how the short-run static stability conditions of the two-sector growth model can be derived by converting the problem into a two-person, two-good exchange model. It is shown that the only necessary and sufficient condition for short-run stability is the Marshall-Lerner condition, and that the Drandakis (sufficient) condition follows easily from the former.]